2022
DOI: 10.3389/fendo.2022.1059085
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomic integrity and the nuclear epigenome in health and disease

Abstract: Bidirectional crosstalk between the nuclear and mitochondrial genomes is essential for proper cell functioning. Mitochondrial DNA copy number (mtDNA-CN) and heteroplasmy influence mitochondrial function, which can influence the nuclear genome and contribute to health and disease.Evidence shows that mtDNA-CN and heteroplasmic variation are associated with aging, complex disease, and all-cause mortality. Further, the nuclear epigenome may mediate the effects of mtDNA variation on disease. In this way, mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Evaluation of the relative mtDNA quantity lacks the evidence of gene integrity and functional assessment. Mitochondria display uniparental inheritance to reduce heteroplasmy, exhibiting a genetic bottleneck to prevent possible deleterious mutants in offspring ( 43 , 44 ). However, mtDNA has a higher mutation frequency due to the insufficient repairing system and higher oxidative stress, the effect derived from these heteroplasmic mitochondria involving de novo variants in early-stage embryos derived from women without inherited mitochondrial disease remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the relative mtDNA quantity lacks the evidence of gene integrity and functional assessment. Mitochondria display uniparental inheritance to reduce heteroplasmy, exhibiting a genetic bottleneck to prevent possible deleterious mutants in offspring ( 43 , 44 ). However, mtDNA has a higher mutation frequency due to the insufficient repairing system and higher oxidative stress, the effect derived from these heteroplasmic mitochondria involving de novo variants in early-stage embryos derived from women without inherited mitochondrial disease remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…These dynamics have also been found to be influenced by environmental stimuli [76]. It has been proposed that these environmental stimuli affect the bidirectional cross-talk between the mitochondrial and nuclear genome through several key mitochondrial metabolites [77]. Here, we identify biological pathways in relation to these associations and highlight key targets for further research.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the dynamic interplay between nuclear and mitochondrial genomes can also influence an organism's phenotype [26]. Using cultured cybrid cell lines harboring a mitochondrial tRNA Leu(UUR) mutation (A3243G), Kopinski et al [26] showed that heteroplasmy leads to diminished acetyl coA generation and concomitant alterations in histone acetylation (i.e., retrograde signaling; mitochondria to the nucleus) [27]. Heteroplasmy frequency has also been shown to play a role in the corresponding phenotype in humans, with low levels (20-30%) in the mitochondrial tRNA Leu(UUR) gene (A3243G) leading to the development of type 2 diabetes and high levels (80-90%) leading to deadly perinatal diseases [7].…”
Section: Discussionmentioning
confidence: 99%